Information technology India's tommorrow - Vittal, N; Mahalingam, S (New Delhi Manas, 2001)
Information technology is India's tomorrow, as pointed out by our Prime Minister, Shri A.B.Vajpayee. Information tech nology is today at the top of India's agenda as an important tool for modernisation of the economy.The present book highlights India's vi
Keywords: Information technology; Technology and state; Technological innovtions